2008
DOI: 10.1590/s1678-77572008000300007
|View full text |Cite
|
Sign up to set email alerts
|

Enamel susceptibility to red wine staining after 35% hydrogen peroxide bleaching

Abstract: Concern has been expressed regarding the staining of enamel surface by different beverages after bleaching. This study investigated the influence of 35% hydrogen peroxide bleaching agents on enamel surface stained with wine after whitening treatments. Flat and polished bovine enamel surfaces were submitted to two commercially available 35% hydrogen peroxide bleaching agents or kept in 100% humidity, as a control group (n = 10). Specimens of all groups were immersed in red wine for 48 h at 37°C, immediately, 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
18

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 19 publications
3
59
1
18
Order By: Relevance
“…Nano-HAP was synthesized in a wet condition according to the method of Boanini et al, 28 with some modifications. 29 4 OH, was added drop-wise under stirring. The precipitate was maintained in contact with the reaction solution for 5 hours at 90°C under stirring, and then, centrifuged at 1800 g for 10 minutes.…”
Section: Synthesis Of Nano-hapmentioning
confidence: 99%
See 1 more Smart Citation
“…Nano-HAP was synthesized in a wet condition according to the method of Boanini et al, 28 with some modifications. 29 4 OH, was added drop-wise under stirring. The precipitate was maintained in contact with the reaction solution for 5 hours at 90°C under stirring, and then, centrifuged at 1800 g for 10 minutes.…”
Section: Synthesis Of Nano-hapmentioning
confidence: 99%
“…3,4 Peroxide bleaching agents have the ability to penetrate into the dental structure 5 and produce free radicals 6 that oxidize colored organic molecules. 7 Hydrogen peroxide has a low molecular weight chain and, in contact with saliva, it decomposes into water and oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…28 It has been shown that post bleaching, the susceptibility of enamel to red wine staining increases and post bleaching red wine causes greater staining than coffee. 29,30 Red wine also stains composite more than tea or coffee. 31 …”
Section: Traumamentioning
confidence: 99%
“…Entre sus componentes se encuentran: agua, azúcar, edulcorantes, ácidos (ortofosfórico, cítrico, má-lico, tartárico), cafeína, colorantes, saborizantes, dióxi-do de carbono, conservantes y sodio [8][9][10]. El ácido ortofosfórico es una sustancia altamente corrosiva que tiene la capacidad de disolver sales de calcio, magnesio y sodio, lo que origina desmineralización en el esmalte dental en las personas que ingieren productos que lo contienen [10].…”
Section: Introductionunclassified